2020
DOI: 10.1080/13854046.2020.1810323
|View full text |Cite|
|
Sign up to set email alerts
|

A survey of international clinical teleneuropsychology service provision prior to and in the context of COVID-19

Abstract: Objective: Despite expansion of telecommunication strategies across health services and data supporting feasibility of videoconference-based neuropsychological assessment, relatively little is known about teleneuropsychology (TeleNP) use in practice. The current COVID-19 pandemic provides an opportunity for greater use of TeleNP and understanding of neuropsychologists' experience with this unique assessment medium. Methods: During the course of a no-cost global webinar related to practical/ethical consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…Chi-square and Phi comparing response frequencies related to telehealth prior to March 13 (142/944 ¼ 15%) versus on or after that date (68/164 ¼ 41.5%) were significant (Chi-square ¼ 37.6; p < .001; Phi ¼ À.169; p < .001; Hedge's g ¼ .34), indicating that the transition had likely already begun by the time the survey website was closed. This finding is consistent with contemporaneous INS webinar survey findings showing that by April 2, 2020 a substantial portion of neuropsychologists internationally had either already begun moving to provision of telehealth services or intended to do so (Hammers et al, 2020). 39.1 Note.…”
Section: Influence Of Current Procedural Terminology (Cpt) Changes Onsupporting
confidence: 77%
“…Chi-square and Phi comparing response frequencies related to telehealth prior to March 13 (142/944 ¼ 15%) versus on or after that date (68/164 ¼ 41.5%) were significant (Chi-square ¼ 37.6; p < .001; Phi ¼ À.169; p < .001; Hedge's g ¼ .34), indicating that the transition had likely already begun by the time the survey website was closed. This finding is consistent with contemporaneous INS webinar survey findings showing that by April 2, 2020 a substantial portion of neuropsychologists internationally had either already begun moving to provision of telehealth services or intended to do so (Hammers et al, 2020). 39.1 Note.…”
Section: Influence Of Current Procedural Terminology (Cpt) Changes Onsupporting
confidence: 77%
“…In terms of overall remote assessment prior to the pandemic, our results did not match that of Hammers et al [23] who found a self-reported use of video neuropsychological assessment of 11% prior to the pandemic, whereas we found that rates of remote assessment were less than 1% across the whole sample. In addition, Hammers et al [23] found that there was no significant increase in video usage (from 11% to 15%). This may be because of differences in the respondent samples.…”
Section: Discussioncontrasting
confidence: 99%
“…There were statistically more video and telephone assessments of cognition since the pandemic. This in line with what recent research has shown in other samples [21,23]. In terms of overall remote assessment prior to the pandemic, our results did not match that of Hammers et al [23] who found a self-reported use of video neuropsychological assessment of 11% prior to the pandemic, whereas we found that rates of remote assessment were less than 1% across the whole sample.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…40 Some reported they will continue to use virtual assessment strategies beyond the COVID-19 pandemic. 41 While challenges should be considered, telehealth presents another avenue for pediatricians recommending patients to specialized treatment.…”
Section: Special Populationsmentioning
confidence: 99%